2022
DOI: 10.3390/tropicalmed7080199
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Well-Being of Elderly Migrants in Dongguan: The Role of Residential Environment

Abstract: To examine the association between community and individual-level residential environment in relation to subjective well-being (SWB) amongst 470 elderly migrants in China, this community-based survey was conducted. The manner and extent to which the SWB of these elderly migrants is influenced by their residential environment was the main area of focus. The Scale of Happiness of the Memorial University of Newfoundland was used to assess SWB. SWB was found to be associated significantly with environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…For elderly people, this environment is not only their residence but also the primary setting for most of their activities [15][16][17][18]. Moreover, current research has confirmed the influence of the built environment on the health of the elderly in many ways, especially in terms of the physical environment [19][20][21]. Studies have explored various built environmental factors affecting the physical and mental health of the elderly, including the density, availability, and accessibility of activity facilities.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…For elderly people, this environment is not only their residence but also the primary setting for most of their activities [15][16][17][18]. Moreover, current research has confirmed the influence of the built environment on the health of the elderly in many ways, especially in terms of the physical environment [19][20][21]. Studies have explored various built environmental factors affecting the physical and mental health of the elderly, including the density, availability, and accessibility of activity facilities.…”
Section: Introductionmentioning
confidence: 68%
“…When it comes to the built environment, the mix of land use, health facilities, and leisure facilities exerted a positive impact on SWB, while the density of financial facilities seemed to have a negative influence on SWB [19]. Previous research has found that accessibility to facilities such as medical centers, banks, and parks in the neighborhood is associated with the well-being of the elderly [19,32,33]. Favorable living environments and convenient infrastructure are important for SWB [19].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…(2) The current research on the built environment and residential satisfaction does not sufficiently consider environmental factors and especially lacks a measurement of the design dimension. Wu [33] Liu [34] Wen [15] Personal properties…”
Section: Literature Summarymentioning
confidence: 99%